Peningkatan kemampuan pola bilangan mahasiswa dengan LKM elektronik bermuatan etnomatematika dan bahasa inggris - Hartono, Hartono; Putra, Muhammad Iqbal Ripo; Susiaty, Utin Desy (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The purpose of this study was to determine the increase of students' numeracy patterning skills with ethnomathematical and English-laden electronic LKM. This research is an experimental study with a one group pretest-posttest design. The sample in this study was 16 fourth semester students of the Mathematics Education Study Program, IKIP PGRI Pontianak with simple random sampling technique. The results showed that the students obtained the pretest and posttest scores for the ability of number patterns with an average of 55,94 and 73,44. After applying learning with electronic LKM containing ethnomathematics and English on the ability of student numbers patterns to get a value of t = 6,139 where = 0.05 with t arithmetic > t table (6,139 > 1,753) then H0 is rejected. Thus, learning with ethnomathematical and English-laden electronic LKM can improve students' numeracy pattern skills.